Geology of the Lesser Himalayan and Higher Himalayan Crystalline sequences of the Everest area along the Dudh Koshi valley, eastern Nepal Himalaya - Rai, SM; Yoshida, M; Upreti, BN; Ulak, PD (Journal of Nepal Geological Society, 2008)
The 40 km sector from Kharikhola to Gorakshep along the Dudh Koshi valley is occupied by the Lesser Himalayan Metasedimentary Sequence (LHS) in the south and the Higher Himalayan Crystalline Sequence (HHCS) in the north, with the Main Central Thrust (MCT) between the above two sequences running at about 2.5 km north from Kharikhola. All rock units of the LHS below the MCT dip towards NNE while the rocks of the HHCS immediately above the MCT dip northwards; further north in the middle section, they dip generally ENE to ESE and megascopic synclinal and anticlinal folds. The main rock types in the LHS are green-schist and lower amphibolite grade metamorphic rocks. They include fine-grained garnet-chlorite-muscovite phyllite, metasandstone and coarse-grained Proterozoic granitic augen gneiss in the structural lower section (southern part). In the upper section (northern part), the rocks are medium grained garnet schist, garnet-muscovite-biotite-graphite schist, and quartzite. Immediate below the MCT, the rocks are found to be highly sheared and seem to be gneiss. S-C structures are prominent showing the south sense of shearing. The rocks of the HHCS are well foliated, amphibolite grade metamorphic rocks which are intruded by Palaeozoic and Tertiary granitoids. The metamorphic rocks are garnet gneiss, garnet-kyanite gneiss, garnet-sillimanite-biotite gneiss, quartzite, schist, amphibolite and marble. Granite, pegmatite and deformed pegmatite are the igneous rocks. In the upper section, south of Gokyo-Ri, very coarse grained; highly sheared augen gneisses of about 300 m thick are exposed. These rocks are pinkish in color due to abundant pink feldspars. This gneiss could be the Cambro-ordovician granite. The middle section surrounding Namche Bazar is dominated by migmatite with migmatitic biotite gneiss, augen gneiss, granitic gneiss, all carrying more or less sillimanite. The amount of migmatitic granite decreases southward. The lower section of the HHCS south of Jorsalle is mostly covered by biotite gneiss with or without garnet and sillimanite. Tourmaline-bearing biotite-muscovite granite is common throughout the middle and lower sections, cross cutting the gneisses and migmatite. The host rocks are folded with the development of major foliation during the syn-MCT deformation prior to the intrusion of the granitic pegmatite. Sometimes, pegmatite carries cleavage, which could be due to late deformation. Some foliated pegmatite is considered to be partially re-melted foliated granite of earlier generation. The early granitic pegmatite is also folded with host rocks. The relationship of folded pegmatite with host rocks, the development of cleavage in pegmatite and porphyroblasts developed along the foliation plane of gneiss show that the major foliation was first intruded by two mica-tourmaline pegmatite (Mu-rich) and then both of them were folded together, resulting in the development of the cleavage as well as flattening of the porphyroblasts. This deformation could be of the post-MCT. Pegmatite locally shows contact effect along with shearing; e. g., coarsening of biotite clot is observed in some biotite schist near the contact with a pegmatite intrusion. This phenomenon is considered to reflect the late stage activity of the MCT associated with the pegmatite intrusion. In some places coarse-grained biotite schist occurs intruded by tourmaline-biotite pegmatite dyke, while in other places, fine grained biotite schist is seen apart from the intrusion. There are a variety of occurrences of folding, foliation, schistosity and cleavage, in relation to augen structure, migmatitic pegmatite and tourmaline granite. Related observations of their relationships will enrich our knowledge on the tectono-metamorphic evolution of the HHCS. The gneisses of the HHCS carry dominant foliation and show a variety of mesoscopic folds. Earliest isoclinal reclined folds, earlier tight plunging folds, and later open and kink upright folds are identified. Some of these structures are considered to be pre-MCT, and some others are found to be syn-MCT deformations. The SSW and SSE plunging mineral lineation marked by mica and sillimanite is developed, possibly related to the movement of the MCT. The Tertiary tourmaline granite cutting across gneisses suffers upright folding and carries cleavage structure parallel to the axial surface of the fold. In some outcrops, interesting relationships among mesoscopic structures, pegmatite intrusion and potash-feldspar porphyroblasts are observed. The highly foliated ductile area shows the different metamorphic episodes. The grade of metamorphism in this area increases towards the upper section of the zone of the HHCS from the MCT . The P-T conditions below the MCT in this region show the inverse metamorphism in the rocks of the LHS. The development of the MCT, the inverse metamorphism and Miocene granitic intrusion in the higher section are genetically related. From the field observation of the middle section of the HHCS, garnet crystals are transformed to chlorite, indicating the effect of retrograde metamorphism. It could be related either or both to the latestage activity of the MCT and/or to the normal faulting (South Tibetan Detachment Fault) event between the HHCS and Tibetan-Tethys Sedimentary Sequence. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.11